2022
DOI: 10.1016/j.jped.2021.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Association between breastfeeding and complementary feeding in pre-pandemic and pandemic COVID-19 times: Maternar cohort study

Abstract: Objective Evaluate the association between breastfeeding, exclusive breastfeeding at six months and the introduction of complementary feeding and the pre-pandemic and COVID-19 pandemic periods. Methods Cohort study conducted with puerperal women and their newborns in the immediate postpartum period at a reference maternity hospital in Southern Brazil between 2018-2020. The COVID-19 pandemic period and the need to work outside the home during restricted circulation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Mothers who have been diagnosed with COVID-19 were more likely to introduce complementary foods to their children before 6 months of age. According to a cohort study conducted in Brazil, the introduction of complementary feeding before the 6th month of life occurs more likely among the interviewed women during the COVID-19 pandemic [ 55 ]. Furtherly, a case-control study conducted in Northeastern Italy found that women in the COVID-19 group had a 20% higher chance of introducing solid foods before 6-month [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who have been diagnosed with COVID-19 were more likely to introduce complementary foods to their children before 6 months of age. According to a cohort study conducted in Brazil, the introduction of complementary feeding before the 6th month of life occurs more likely among the interviewed women during the COVID-19 pandemic [ 55 ]. Furtherly, a case-control study conducted in Northeastern Italy found that women in the COVID-19 group had a 20% higher chance of introducing solid foods before 6-month [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a preprint report on qualitative interviews of mothers conducted during a formula shortage in 2022 in Washington, DC, several mothers reported resorting to deleterious formula‐feeding practices such as thinning formula or introducing solids earlier than they had originally intended (Sylvetsky et al, 2022). A study conducted in Brazil reported that infants born postpandemic (compared to prepandemic) had a significantly higher risk of being introduced to complementary foods before the recommended age (Holand et al, 2022). While these reports are concerning, little is known about how formula shortages reported in the United States due to the COVID‐19 pandemic impacted formula‐feeding behaviour and infant health.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential explanation is heightened fear of pregnancy complications and overall anxiety due to COVID-19. [27][28][29] Rates of labor induction were also significantly higher among the pandemic-exposed cohort, an expected finding given a widespread increase in scheduled inductions in an attempt to control a portion of hospital volume during this hightransmission risk time period. 30 During the pandemic, our institution's policy shifted to encourage 39-week elective labor induction.…”
Section: Resultsmentioning
confidence: 76%
“…Protocols that streamlined prenatal care services during the pandemic may have reduced inequities in care delivery and contributed to increased delivery of prenatal screening observed in this study. Other possible reasons for increased diabetes screening during the pandemic include heightened anxieties regarding pregnancy complications during the pandemic [27][28][29] and less travel time and costs for patients utilizing telehealth. This could increase attendance at the reduced number of essential in-person appointments where patients can receive recommended services such as diabetes screening and ultrasounds during the course of prenatal care.…”
Section: Discussionmentioning
confidence: 99%